Heterogeneous ion exchange membranes with silver based additive - Stránská, Eliška; Weinertová, Kristýna (University of Pardubice, 2019)
Heterogeneous anion-exchange and cation-exchange membranes with the addition of antimicrobial additive Sanitized BC A 21-41 (silver in the glass matrix), reinforced with polyester fabric (AM-PES Sanitized or CM-PES Sanitized) were prepared on the pilot lamination line in our company. Basic physical and electrochemical properties of membranes, antimicrobial activity after long-term desalination in the electrodialysis unit were characterized. The release of silver from antimicrobial additive into the solutions was also determined when using atomic emission spectroscopy. Prepared membranes modified with antimicrobial additive have shown the improved antimicrobial properties over commercial membranes Ralex® in terms of the print on agar plates and the determination of inhibition zones for Escherichia coli and Staphylococcus aureus. Sanitized additive was not washed out from the membranes even after long-term electrodialysis tests. In addition, the prepared membranes have exhibited lower areal resistance due to the reduced thickness in the dry and swollen state, thus contributing to the reduction of energy needed for electrodialysis.
Keywords: ion-exchange membrane; antimicrobial activity; plastic additives